Sosialisasi GERMAS (Gerakan Masyarakat Hidup Sehat) Pada Kader Posyandu di Wilayah Kerja Puskesmas Alas - Kusuma, Arifa; Reni Handayani, Asri; Maliga, Iga (Jurnal Pengabdian Masyarakat Nusantara, 2022)
Health development is essentially a work carried out by all nations whose goal is to increase everyone's awareness, desire and ability to live healthily in order to achieve the highest degree of public health. Today's health problems are the result of an unhealthy lifestyle coupled with environmental sanitation and lack of access to clean water in many areas. In addition to the quality of environmental and health services and infrastructure, the family is an important part of disease prevention. GERMAS (Healthy Living Community Movement) is a systematic and planned activity carried out by all ethnic groups with awareness, desire and ability to live a healthy life to improve the quality of life. The purpose of community service activities is to inform people around the world. Board of directors Staff with GERMAS expertise. The method is lecture and discussion. The event was attended by 48 people. The activity was carried out on December 2, 2022 for 1 hour 20 minutes. The series of events of this activity are open, subject matter, discussion and closing. As a result of this activity, the cadres will receive information about GERMAS to be disseminated to the community and the GERMAS program can continue to be implemented in every community to create a physically and mentally healthy society. The GERMAS program can reduce the burden of disease, reduce the financial burden on health services due to increased disease and health service costs.